Field notes contributed by Dennis L. Carter, August 1, 2000 - Carter, Dennis L.et al (2000)
Summer report of birds and locations contributed by Dennis L. Carter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 2000. Epson - sheet feed/flatbed